Analysis of process-induced deformations in thermoplastic composite materials. (September 2014) - Brauner, Christian; Peters, Christian; Brandwein, Franziska; Herrmann, Axel S
The thermoforming process is a manufacturing method to produce fibre-reinforced thermoplastic components within short cycle times (<2 min). During this process, the anisotropic material behaviour provokes residual stresses which furthermore induce unwanted deformations. Thereby, at the beginning, newly produced geometries have a quite high reject rate and the process parameters have to be adjusted iteratively. Thus, an analysis of the process-induced deformations has been carried out to investigate the connections between process parameters and final geometry. In this case, an L-angle bracket has been observed which shows a spring-in effect after the thermoforming process. For the experimental approach, the semi-crystalline polyphenylenesulphide was used as thermoplastic matrix material. In particular, the crystallisation kinetics of this polymer is described by adjusting Nakamura's crystallisation model to different cooling rates. And furthermore, a simulation strategy has been developed to include the crystallisation behaviour in a thermal and mechanical analysis. The results of these analyses have been compared and evaluated with the outcomes of the experimental approach. Finally, some opportunities for future studies will be introduced to provide a way for improving the simulation analysis.